(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the peak of present competitive world, the contract labours are serving in every nation. The trained agencies are providing this contract labours in the formal basis of curtain trainings and skills along with prescriber instructions. At the view point of Ballari district in Karnataka, there is a huge great demand for contract labour. Because this district is very rich in mining source and economically it is a developing district in major aspects. Hence there are a many dimensions, degrees and dilemmas between contract labours, labour associations, agencies, government pressers along with political interference in the core of socio-economic status of contract labours. In this paper, the study has carried by both qualitative and quantitative methods as well as primary and secondary data. As well it has framed under the objective to find about the working patterns of contract labourers in industries. Along with the hypothesis significantly, the majority of the contract labourers in industries are joined under contractor as well mainstream, they have 8 hours of working time per day in the core of working patrons. Thus the paper tried to discuss about the challenges of contract labours together with working hours per day of them with the help of relevant table and chart. Even there have identified curtain findings and coated some suggestions as accordingly the topic.